Exploring public attention and sentiment toward carbon neutrality: evidence from Chinese social media Sina Weibo - Wang, Bo; Jiang, Zixiao; Cheng, Dawei; Wang, Ziao (Frontiers in Psychology, 2023)
Introduction Exploring the public’s cognition toward carbon neutrality is conducive to improving the quality and effectiveness of policymaking, and promoting the realization of carbon neutrality goals. This study aims to explore the public’s attention and sentiment toward carbon neutrality from the perspective of social psychology. Methods Using posts on carbon neutrality from the Chinese social media platform Sina Weibo as the data source, this study uses statistical analysis, the Mann-Kendall method, keyword analysis, the BERT model, and the LDA model to explore public attention and sentiment. Results The results show that: (1) men, people living east of the Hu line (economically developed regions), and the public in the energy finance market are more concerned about carbon neutrality; (2) high public attention and great dynamic changes in public attention toward carbon neutrality could be trigged by highly credible government or international governmental organizations’ information; (3) public sentiment toward carbon neutrality is mostly positive; however, specific topics affect public sentiment differently. Discussion The research results contribute to policymakers’ better understanding of the trend of public attention and sentiment toward carbon neutrality, and support improvements in the quality and impact of policymaking.